Peri-operative Outcomes of Neonatal Surgeries at an Academic Institution - Essa, Laika (University of the Witwatersrand, Johannesburg, 2024)
Background Neonates undergoing anaesthesia have a high incidence of peri-operative critical events. In South Africa, there is a higher rate of peri-operative morbidity and mortality compared to high income countries. The rate of intra-operative critical events is unknown. Our aim was to investigate the incidence of peri-operative critical events and to identify factors associated with poor outcomes. Methods A retrospective, cross-sectional study was carried out at a quaternary academic hospital in Johannesburg, South Africa. A sample of 100 neonates was used where an anaesthetic was performed for an emergency or elective surgery. The neonates’ demographics were described and risk factors for peri-operative critical events were identified. Associations between risk factors and the prevalence of peri-operative critical events, morbidity and mortality were assessed. Results Intra-operative critical events occurred in 78% of neonates. Intra-operative critical events included cardiovascular (50%), body temperature correction (47%), glucose or electrolyte correction (41%), airway (25%), and oxygenation (13%) events. Prematurity (<37 weeks) and low birth weight (<2500g) were associated with a higher incidence of critical events; OR (95% CI) 8.84 (2.92 – 33.2) p<0.001 and OR (95% CI) 9.10 (2.81, 41.1) p<0.001 respectively. Post-operative morbidity was found in 78% of neonates and mortality in 31%. Post-operative infection occurred in 66% of neonates and contributed to 46% of deaths. Conclusion There is a higher incidence of critical events in our neonatal surgical population compared to high income countries. Prematurity and LBW are significant pre-operative risk factors for critical events. Post-operative infection contributed significantly to morbidity and mortality.
A research report submitted in fulfillment of the requirements for the Master of Medicine, In the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Mortality; morbidity; neonatal anaesthesia; neonatal surgery; outcomes; peri-operative; SDG-3: Good health and well-being